Investigating the Pathological Mechanisms Underlying the Development of Diabetic Complications, Such as Neuropathy, Nephropathy and Retinopathy - Razwan Ashraf, Jawad Ullah, Abdul Haleem, Husnain Hashim, Muhammad Naveed, Nusrat Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetes mellitus stands as a formidable global health challenge, affecting millions worldwide and imposing a significant burden on healthcare systems. While its hallmark is dysregulation of blood glucose levels, the repercussions extend far beyond glycemic control. Objective: to find the pathological mechanisms underlying the development of diabetic complications, such as neuropathy, nephropathy, and retinopathy. Study Design: Retrospective study. Place and Duration of Study: Aziz Bhatti Shaheed Teaching Hospital, Gujrat from 1st August 2022 to 31st July 2023. Methodology: Five hundred and fifty patients diagnosed with diabetes mellitus, who were receiving care at a tertiary healthcare facility were enrolled. Medical records of eligible patients were meticulously reviewed by trained healthcare professionals to extract pertinent information related to demographics, diabetes duration, glycemic control (e.g. HbA1c levels), comorbidities, medication history, and presence of diabetic complications (neuropathy, nephropathy, retinopathy, etc). Results: The mean age was 58.5±9.21 years. On average, patients had been living with diabetes for 10.3±6.78 years, with a mean HbA1c level of 8.6±1.23%, indicating moderate glycemic control. These results offer insights into the demographic and clinical characteristics of the patient population under investigation. 42% experienced peripheral symptoms indicative of neuropathy, while 28% showed abnormal nerve conduction. Nephropathy was observed with elevated urinary albumin excretion in 36% of patients and reduced estimated glomerular filtration rate (eGFR) in 24%. Additionally, 48% of patients were diagnosed with retinopathy. Conclusion: The significant relation of diabetic complications, including neuropathy, nephropathy, and retinopathy, among patients with diabetes mellitus. Poor glycemic control, prolonged diabetes duration, and the presence of comorbidities emerged as significant risk factors for the development of these complications. Keywords: Diabetes, Complications, Neuropathy, Nephropathy, Retinopathy, Pathological Mechanisms, Genomic analysis, Therapeutic intervention, Prevention strategies